2015
DOI: 10.3109/14017431.2015.1039571
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the mechanisms of diastolic dysfunction in patients with type 2 diabetes

Abstract: Our study showed that serum sRAGE level was significantly lower in type 2 diabetic patients aged < 50 years old. Also, sRAGE has negative correlation with the duration of diabetes and it was significantly associated with the presence of diastolic dysfunction in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the contrary, recent clinical studies noted the importance of left ventricular diastolic dysfunction in the pathogenesis of HF. Furthermore, some researchers have indicated that AGEs or RAGE affected left ventricular diastolic function [ 26 , 27 ]. Wang et al reported the significant relationship of E/e′ as a marker of left ventricular diastolic function and skin AF in subjects at risk for cardiovascular diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, recent clinical studies noted the importance of left ventricular diastolic dysfunction in the pathogenesis of HF. Furthermore, some researchers have indicated that AGEs or RAGE affected left ventricular diastolic function [ 26 , 27 ]. Wang et al reported the significant relationship of E/e′ as a marker of left ventricular diastolic function and skin AF in subjects at risk for cardiovascular diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also revealed the E/e' ratio as a predictor of first HF hospitalization in patients with HFpEF. However, AGEs/AGE receptors (RAGEs) may affect left ventricular diastolic function through several pathways [25,26]. Moreover, several clinical reports exist demonstrating a significant relationship of left ventricular diastolic function and skin AF [27,28].…”
Section: Discussionmentioning
confidence: 99%